2021
DOI: 10.32598/jrh.11.3.1224.3
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Smartphone Use and Aggressive Behavior Among University Students: The Mediating Role of Sleep Disturbance

Abstract: Background: Despite several benefits, research has found that problematic smartphone use is positively associated with behavioral problems. However, the internal mechanisms underlying this relationship need further investigation. So, the current study aimed to investigate the mediating role of sleep disturbance in the relationship between problematic smartphone use and aggression. Methods: The research design was descriptive-correlational. Also, the study population included the male university students of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…In a separate vein, excessive smartphone use has been shown to be associated with poorer sleep quality and shorter sleep duration [ 11 , 12 ], which implicate a loss of control over emotions and aggressive impulses [ 13 ]. In line with this notion, studies have found that problematic smartphone users experience sleep disturbance and display greater aggressive behaviors [ 2 ]. Therefore, maladaptive smartphone use would likely implicate heightened aggression.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a separate vein, excessive smartphone use has been shown to be associated with poorer sleep quality and shorter sleep duration [ 11 , 12 ], which implicate a loss of control over emotions and aggressive impulses [ 13 ]. In line with this notion, studies have found that problematic smartphone users experience sleep disturbance and display greater aggressive behaviors [ 2 ]. Therefore, maladaptive smartphone use would likely implicate heightened aggression.…”
Section: Introductionmentioning
confidence: 89%
“…However, relatively little research has focused on the relation between smartphone use and sociobehavioral outcomes. Excessive smartphone use adversely influences daily activities such as sleep quality [ 2 ], which in turn induces stress, frustration, and negative affect. Given that these negative emotions heighten one’s aggressive tendencies [ 3 , 4 ], it is plausible that excessive or addictive smartphone use may be related to aggression, which consists of instrumental (i.e., physical and verbal aggression), affective (i.e., anger) and cognitive (i.e., hostility) components [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it can lead to poor academic performance. According to Zarei ( 2021 ), one of the important factors impacting the aggressive behavior of university students is problematic smartphone use. According to researchers, focusing on students with smartphone addiction and early intervention for aggression is critical.…”
Section: Introductionmentioning
confidence: 99%
“…(15) Studies have shown that there is a positive relationship between problematic use of mobile phones and aggression. (16) Studies show that people with aggressive characteristics are addicted to smartphones. (17) Trust in technology to increase social communication may have psychological consequences, such as creating technological dependencies, extroverted personality traits (deepening interpersonal interactions), and anger.…”
Section: Introductionmentioning
confidence: 99%